Assessing seasonal and interannual changes in carbonate chemistry across two time-series sites in the North Western Mediterranean Sea - Wimart-Rousseau, Cathy; Wagener, Thibaut; Bosse, Anthony; Raimbault, Patrick; Coppola, Laurent; Fourrier, Marine; Ulses, Caroline; Lefèvre, Dominique (Frontiers in Marine Science, 2023)
Sustained time-series measurements are crucial to understand changes in oceanic carbonate chemistry. In the North Western Mediterranean Sea, the temporal evolution of the carbonate system is here investigated based on two 10-year time-series (between January 2010 and December 2019) of monthly carbonate parameters measurements at two sampling sites in the Ligurian Sea (ANTARES and DYFAMED). At seasonal timescale, the seawater partial pressure of CO2 (pCO2) within the mixed layer is mostly driven by temperature at both sites, and biological processes as stated by the observed relationships between total inorganic carbon (CT), nitrate and temperature. This study suggests also that mixing and water masses advection could play a role in modulating the CT content. At decadal timescale, significant changes in ocean chemistry are observed with increasing trends in CT (+3.2 ± 0.9 µmol.kg −1 .a −1 -ANTARES; +1.6 ± 0.8 µmol.kg −1 .a −1 -DYFAMED), associated with increasing pCO2 trends and decreasing trends in pH. The magnitude of the increasing trend in CT at DYFAMED is consistent with the increase in atmospheric pCO2 and the anthropogenic carbon transport of water originating from the Atlantic Ocean, while the higher trends observed at the ANTARES site could be related to the hydrological variability induced by the variability of the Northern Current.